Ethical Resonance - Prasad, Leela 1966- (2019)
This essay defines ethical resonance through an ethnographic interlude that paves the way for a broader theorization of the concept. It begins by contextually recounting the story of an individual who had stayed at Sevagram, Mahatma Gandhi's last ashram in 1944, shadowing Gandhi for some 20 days. The young man's brief meeting with Gandhi in which Gandhi uttered only one sentence transformed him for his lifetime. I reflect on the experience and its narrative qualities to explore the broader question of why one is moved, and moved enough to be altered. I propose that the theorization of resonance in modern physics, in phenomenology, and in 11th-century Sanskrit poetics is productive for understanding the subjective and the trans-subjective elements that underlie ethical persuasion. I argue that the idea of resonance helps bridge the affective and the aesthetic in moral self-formation that occurs in everyday life.
Keywords: Anandavardhana; Gandhi; aftertone; Duration; ethical resonance; Phenomenology; Physics